2007
DOI: 10.1901/jaba.2007.151-05
|View full text |Cite
|
Sign up to set email alerts
|

Further Examination of Factors That Influence Preference for Positive Versus Negative Reinforcement

Abstract: Factors that influence choice between qualitatively different reinforcers (e.g., a food item or a break from work) are important to consider when arranging treatments for problem behavior. Previous findings indicate that children who engage in problem behavior maintained by escape from demands may choose a food item over the functional reinforcer during treatment (DeLeon, Neidert, Anders, & Rodriguez-Catter, 2001;Lalli et al., 1999). However, a number of variables may influence choice between concurrently avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…These interventions use the reinforcer identified as maintaining the problem behavior to reinforce appropriate responses. Although these methods often decrease problem behavior, researchers also have found that changing consequences not necessarily related to the ones maintaining the escape behavior may be equally effective (e.g., Golonka et al, 2000;Kodak, Lerman, Volkert, & Trosclair, 2007;Lalli et al, 1999). For example, researchers working with adults and children with developmental Hawkins, Axelrod / Using FBA to Improve Homework Behavior 843 delays have found that positive reinforcement for appropriate behavior can effectively decrease escape-maintained behavior.…”
Section: Escape-maintained Behaviormentioning
confidence: 99%
“…These interventions use the reinforcer identified as maintaining the problem behavior to reinforce appropriate responses. Although these methods often decrease problem behavior, researchers also have found that changing consequences not necessarily related to the ones maintaining the escape behavior may be equally effective (e.g., Golonka et al, 2000;Kodak, Lerman, Volkert, & Trosclair, 2007;Lalli et al, 1999). For example, researchers working with adults and children with developmental Hawkins, Axelrod / Using FBA to Improve Homework Behavior 843 delays have found that positive reinforcement for appropriate behavior can effectively decrease escape-maintained behavior.…”
Section: Escape-maintained Behaviormentioning
confidence: 99%
“…Adicionalmente, poder-se-ia tentar identifi car e/ou manipular as variáveis motivacionais dos participantes [(e.g., saciação e privação (Michael, 1993). Indivídu-os poderiam ser privados/saciados de determinados estímulos (e.g., vídeos reforçadores) por períodos específi cos para se avaliar os efeitos da manipulação das variáveis motivacionais, ao se utilizar vídeos reforçadores, na aquisição da discriminação simples e da reversão)]; (c) Para favorecer a discriminabilidade entre as alternativas, procedimentos envolvendo atraso no reforço ou durações diferentes de reforço poderiam ser incluídos (Hanna & Blackman, 2005), ou até mesmo poderia ser realizado um treino discriminativo antes do procedimento de escolha (Escobal & Goyos, 2015;Kodak, Lerman, Volkert, & Trosclair, 2007); (d) No presente estudo não foi medida a latência média do desempenho nas alternativas durante a avaliação de preferência por tarefas, futuros estudos poderiam avaliar tal medida, pois a latência média de desempenho pode infl uenciar na escolha. O mesmo pode ocorrer com o tempo de duração da consequência e da 'tela preta'.…”
Section: Discussionunclassified
“…In addition, the motivational variables of the participants could be tried to be identifi ed and/or manipulated [(e.g., satiation and deprivation;Michael, 1993). Individuals could be deprived /satiated of certain stimuli (e.g., reinforcer videos) for specifi ed periods to evaluate the effects of manipulation of motivational variables when using reinforcer videos, in the acquisition of simple and reversal discrimination)]; (c) To promote discriminability between the alternatives, procedures involving delayed reinforcement or different reinforcement durations could be included (Hanna & Blackman, 2005), or discriminative training could even be carried out before the choice procedure (Escobal & Goyos, 2015;Kodak, Lerman, Volkert, & Trosclair, 2007); (d) In this study, the average latency performance was not measured in the alternatives during the assessment of preference for tasks. Future studies could assess this measure, as the average latency performance can infl uence the choice.…”
Section: Discussionmentioning
confidence: 99%